Family Planning During and After the West African Ebola Crisis. Issue 1 (16th March 2020) - Bietsch, Kristin; Williamson, Jessica; Reeves, Margaret
Abstract: The West African Ebola outbreak of 2013–2016 had the potential to devastate family planning programs in affected countries, which had made great progress in years prior. We examine monthly provision of family planning service statistics from government sources for Liberia and Sierra Leone from 6 months before the first Ebola case to 24 months after the last Ebola case to measure the impact during and after the epidemic. By calculating the couple‐years of protection from service statistics, we find that family planning distribution declined by 65 percent in Liberia and 23 percent in Sierra Leone at the peak of the epidemic. Two years after Ebola, Liberia's average monthly contraception distribution is 39 percent above precrisis levels, while distribution in Sierra Leone increased by 27 percent, findings echoed in data from the Demographic and Health Survey and Multiple Indicator Cluster Survey. Increased contraceptive use comes from implants in both countries, and injectables in Liberia. This study indicates that the family planning sector can recover, and continue to improve, following a significant disruption and is a lesson in resilience.